Two-Sided Platforms and Biases in Technology Adoption - Jay Pil Choi; Doh-Shin Jeon (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We investigate the relationship between market structure and platforms' incentives to adopt technological innovations in two-sided markets, where platforms may find it optimal to charge zero price on the consumer side and to extract surplus on the advertising side. We consider innovations that affect the two sides in an opposite way. We compare private incentives with social incentives and find that the bias in technology adoption depends crucially on whether the non-negative pricing constraint binds or not. Our results provide a rationale for a tougher competition policy to curb concentration if competition authorities put more weight on consumer surplus in welfare calculations.
Keywords: D40; L10; L50; 330; technology adoption; two-sided platforms; non-negative pricing constraint; pass-through